Friction and Wear Characterizations in Electrospun Nanofibrous Scaffolds for Cartilage Engineering - André Mathias Souza Plath; Mohammad Alinezhadfar; Stephen J. Ferguson (Nano Select, 2025)
ABSTRACT Electrospun nanofibers are promising materials to treat articular cartilage (AC) defects. However, they still have lower mechanical properties than tissue. There are no standard protocols to test friction in electrospun materials. Only a few studies have reported electrospun mats’ coefficient of friction (COF). This work aims to evaluate COF and wear for electrospun mats using a universal testing tribometer. Stainless steel, polyoxymethylene (POM), and rubber balls were rubbed against poly(ε‐caprolactone) (PCL) mats. There was a statistically significant difference between metal and rubber/plastic. This is attributed to surface chemistry. POM countersurfaces were rubbed at 1, 10, and 50 mm/s. The results show a small COF reduction proportional to speed and stick‐and‐slip behavior. Finally, we tested a PCL‐zein‐based material for its water contact angle reduction from 120° to 60°. The results demonstrated the lubrication efficiency (20% COF reduction) and hydrophobic‐hydrophilic contacts (33% COF reduction). The study successfully evaluates electrospun mats’ tribological properties. This is followed by the perspective of shear and friction biostimulation in electrospun surfaces. Furthermore, at the tested loads, the material had AC‐like COFs at boundary lubrication conditions.